Program Up2k (Upaya Peningkatan Pendapatan Keluarga) Terhadap Kesejahteraan Masyarakat Di Kecamatan Sungai Bahar Tahun 2021 - M Nazori; Muhammad Ismail; Ayu Alfarida (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The UP2K program is one of the efforts to improve family welfare and resilience, which is reflected in the increased ability of families to meet family needs. The hope is to improve health conditions, education and skills. The purpose of this study was to determine the increase in the income of the people who took part in the Family Income Increase Business Program (UP2K) in Sungai Bahar District. The research method used is descriptive qualitative method, in which the data collected is in the form of words or pictures. So don't press on the numbers. This research emphasizes more and focuses on process and meaning (the data behind the observed). And from the results of the research is that the condition of people's income before receiving community assistance experienced difficulties and the majority of income and the economy in the Sungai Bahar sub-district were classified as low. Meanwhile, the condition of people's income after receiving economic assistance and community income has improved and increased with the role of the PKK.